A stakeholder perspective on social stability risk of public–private partnerships project for water environmental governance in China: A social network analysis - Wang, Wenke; Guo, Xinlin; Cao, Qilin; Tang, Aomei (Frontiers in Ecology and Evolution, 2023)
The pluralism of stakeholders in PPP project for water environmental governance and the complex interrelationship among stakeholders are the important factors affecting social stability risk. Previous studies have mainly focused on risk identification and assessment. We aim to investigate the key social risks of PPP project for water environmental governance, to understand which social risks stakeholders are concerned about, and what interactions they follow. First, relevant risks and their interrelationships were investigated through a literature review and interviews. Second, the key social stability risks were identified based on social network analysis. Third, strategies were proposed to mitigate the social stability risks. We concluded that controlling the complicated relationships among the government, contractors, project companies, and the public and the media can reduce the social stability risks. The social network analysis framework combining stakeholder management and risk management provides a reference for the management of PPP projects for water environmental governance.